Sistem Otomatisasi Plant Factory dengan Tiga Jenis Tanaman Sayuran Berbeda Berbasis Mikrokontroler dan Android - Hafizh Ramli; Lathifah Arief (CHIPSET, 2021)
Plant Factory is a technology concept that facilitates the formation of an environment that is suitable and good for plant growth, easy to control, does not require a large area of land, and is applied indoors so that it is not affected by outdoor weather conditions. Therefore created a system that automatically controls and monitors environmental conditions such as temperature, humidity and light. This system uses Arduino mega 2560 as a microcontroller, DHT22 temperature and humidity sensors to assess room temperature and humidity, RTC as an indicator of plant irradiation time, a micro SD module as data storage for sensors and actuators, and a Bluetooth module as a medium for data transmission. This actuator consists of a fan to control temperature, a humidifier to control humidity and an LED as a substitute for lighting plants. There are three plants as samples for testing the Plant Factory system, namely spinach, lettuce and mustard greens with each Plant Factory system for these plants. All temperature, humidity and actuator conditions can be monitored via the Android application. The plant factory automation system with three types of vegetable plants based on microcontroller and android is successfully running according to its function.